Analysis of Case Studies on The Crime of Human Trafficking - Alpadly, Achmad Arif; Tafsirudin; Irkham, Yusuf; Karina, Siska; Gunawan, M. Sigit (Ann Publisher, 2024)
The study seeks to investigate the challenges in the enforcement of laws pertaining to human trafficking offenses involving Indonesian migrants. This research addresses legal challenges from a normative perspective grounded in the rule of law inside statutes and regulations. The material utilized in this study is empirical judicial. Field research is undertaken to examine the many legal requirements that are applicable in society. This research indicates a limited number of stakeholders involved, including Indonesian migrant workers, civil registry officials, airport staff, airport officers, and immigration personnel, who can facilitate the passage of Indonesian migrant candidates in terms of rewards. Legal action by the Indonesian migrant protection agency for the postponement of services, revocation of business licenses, recall of written agreements, business operations, and annulment of prospective commercial activities. Migrant workers and foreign laborers are responsible for their expenses. Prolonged initiatives are encouraged under the stringent oversight of Indonesia's labor service provider firms. Human trafficking is governed by Law No. 21 of 2007, which addresses eradicating this crime. The law serves two essential functions in social change: as an instrument of social control and as a method of social engineering. RT, RW, and village institutions contribute to community empowerment in effectively implementing preventative measures. Legal understanding pertains to the comprehension of the regulations established by written law about permissible and impermissible societal conduct.